1999
DOI: 10.1034/j.1399-0012.1999.130413.x
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic retinopathy after combined kidney–pancreas transplantation

Abstract: Diabetic retinopathy (DR) is amenable to good diabetic control; however, only successful pancreas transplantation can achieve sustained normoglycaemia. The aim of this long-term study was to examine the course of DR in insulin-dependent diabetic recipients of a simultaneous kidney and pancreas transplant (SPK). Successful SPK recipients (n = 46) and failed pancreas transplant with a functioning kidney transplant (n = 8) were assessed by baseline and regular post-transplant ophthalmic examinations (n = 432) for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
53
0
7

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(63 citation statements)
references
References 20 publications
3
53
0
7
Order By: Relevance
“…However, many patients still progress to more severe lesions despite improvements in glucose control [4]. After blood glucose normalisation subsequent to simultaneous pancreas-kidney transplantation, a few groups (but not all) observed amelioration of diabetes ocular complications [6][7][8][9][10][11][12][13][14], but it cannot be ruled out that the attendant cure of uraemia might have played an important role [25]. Therefore, studying normoglycaemic pancreas-alone recipients is possibly a better way to assess the effects of normoglycaemia on diabetes complications.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, many patients still progress to more severe lesions despite improvements in glucose control [4]. After blood glucose normalisation subsequent to simultaneous pancreas-kidney transplantation, a few groups (but not all) observed amelioration of diabetes ocular complications [6][7][8][9][10][11][12][13][14], but it cannot be ruled out that the attendant cure of uraemia might have played an important role [25]. Therefore, studying normoglycaemic pancreas-alone recipients is possibly a better way to assess the effects of normoglycaemia on diabetes complications.…”
Section: Discussionmentioning
confidence: 99%
“…Lately, the effects of combined pancreas-kidney transplantation on diabetic retinopathy have been described, and conflicting results reported [6][7][8][9][10][11][12][13][14]. Some work showed no significant change or even progression in retinal complications following combined pancreas-kidney transplantation [6][7][8][9].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…31 Following SPK transplantation, 14% of non-blind eyes showed improvement, 76% remained stable and only 10% progressed further. 32 A separate study reported an improvement in post-transplant visual acuity in 32% of the eyes and frequency/severity of vitreous hemorrhages in 46% of eyes. 31 It may take up to 4 years before noticeable functional improvement in retinopathy and acuity may be observed.…”
Section: Retinopathymentioning
confidence: 99%
“…33 Amelioration of diabetes-associated morbidity-Numerous studies have shown that a successful pancreas transplant can slow micro-vascular complications, including nephropathy, retinopathy and neuropathy. [34][35][36][37] Disappointingly, however, clear evidence has not emerged showing that pancreas transplantation can reverse pre-existing lesions or completely prevent the progression of new ones that are diabetes-related. This could be the result of factors that are independent of glycaemic control.…”
Section: Metabolic Considerationsmentioning
confidence: 99%